Targeting tumor-derived NLRP3 reduces melanoma progression by limiting MDSCs expansion - Tengesdal, Isak W; Menon, Dinoop R; Osborne, Douglas G; Neff, Charles P; Powers, Nicholas E; Gamboni, Fabia; Mauro, Adolfo G; D'Alessandro, Angelo; Stefanoni, Davide; Henen, Morkos A; Mills, Taylor S; De Graaf, Dennis M; et al. (Proceedings of the National Academy of Sciences - PNAS, 2021)
Interleukin-1β (IL-1β)-mediated inflammation suppresses antitumor immunity, leading to the generation of a tumor-permissive environment, tumor growth, and progression. Here, we demonstrate that nucleotide-binding domain, leucine-rich containing family, pyrin domain-containing-3 (NLRP3) inflammasome activation in melanoma is linked to IL-1β production, inflammation, and immunosuppression. Analysis of cancer genome datasets (TCGA and GTEx) revealed greater NLRP3 and IL-1β expression in cutaneous melanoma samples ( = 469) compared to normal skin ( = 324), with a highly significant correlation between NLRP3 and IL-1β ( < 0.0001). We show the formation of the NLRP3 inflammasome in biopsies of metastatic melanoma using fluorescent resonance energy transfer analysis for NLRP3 and apoptosis-associated speck-like protein containing a CARD. In vivo, tumor-associated NLRP3/IL-1 signaling induced expansion of myeloid-derived suppressor cells (MDSCs), leading to reduced natural killer and CD8 T cell activity concomitant with an increased presence of regulatory T (Treg) cells in the primary tumors. Either genetic or pharmacological inhibition of tumor-derived NLRP3 by dapansutrile (OLT1177) was sufficient to reduce MDSCs expansion and to enhance antitumor immunity, resulting in reduced tumor growth. Additionally, we observed that the combination of NLRP3 inhibition and anti-PD-1 treatment significantly increased the antitumor efficacy of the monotherapy by limiting MDSC-mediated T cell suppression and tumor progression. These data show that NLRP3 activation in melanoma cells is a protumor mechanism, which induces MDSCs expansion and immune evasion. We conclude that inhibition of NLRP3 can augment the efficacy of anti-PD-1 therapy.